RANCANG BANGUN PROTOTIPE PEMANTAU KEBOCORAN GAS MENGGUNAKAN SENSOR MQ-6 BERBASIS NodeMCU 8266 - Praja Dwitama, Anandita; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p2, 2021)
Liquefied Petroleum Gas (LPG) leak detection and monitoring system is a step to anticipate the danger of gas leaks. BPBD data for 2016 - 2020 fires due to LPG gas leakage are 50 cases, handling is still manual. The design of this prototype uses the Arduino NodeMCU 8266 module as the main controller. The sensor used by the MQ-6 sensor is suitable for detecting propane and butane gas in LPG. In order for the sensor to work optimally the sensor is set at a distance of 10 cm from the gas source. The prototype uses a solenoid valve which is a valve controlled with AC or DC electric currents through the selenoids. Buzzers and notifications via the telegram application complement the output of the prototype if a gas leak is indicated. The duration of the notification is sent depending on the signal strength of the WiFi / provider used, while the duration of the buzzer sounds as long as the detected gas level exceeds the value of the sensor set. The results achieved in the study, namely the gas leak monitoring prototype using the MQ-6 sensor based on NodeMCU 8266 was very effective. MCU node 8266 can be used to open / close valve electronics automatically. The ideal distance to read the gas leak smoke is 10 cm. The time the notification is sent depends on the signal strength of the WiFi / provider used, in this study it was found 80-92 dbm, the duration of the buzzer sounded as long as the gas level was detected more than 200 ppm.